Covid-19 Era Alternative Strategies: Exploring Blended Learning Methods in Malay Language - Nurul Haniza Samsudin; Nur Azimah Mohd Bukhari; Akhmad Mansur (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2022)
There are no ending signs when it comes to the spreading of COVID-19 worldwide. The cases were increasing and have caused the students of Higher Education to have their studies to be carried out either in hybrid or blended learning. The COVID-19 during the pandemic had affected many sectors and industries and mainly the education industry. The education sector had faced many impacts. As for the higher education sector, the institution had led to factors such as academic stress, anxiety, loss of concentration, and frustration. Today, COVID-19 is still spreading worldwide and, in our country, as well. Malaysia declared it a pandemic in the early stages, but as time passed, Malaysia declared it an endemic. Blended learning would be among the options to pull through during the COVID-19 era, and it is also an alternative strategy to continue teaching and learning. Blended learning includes face-to-face and online teaching. This benefits the learners with dual instruction and learning strategies and this study shares and discusses the design of a blended learning course in teaching and learning language using the Blended Learning Model by Bath & Brouke (2010). The model contains five phases; planning, designing, implementing, reviewing, and improving. This model applies to the subject of Teaching the Malay Language. These courses were registered as required subjects with a total of 24 third-year students. During the planning phase, questionnaires were used to implement the quantitative methods. In the meantime, qualitative methods are used to analyse the document during design, implementation, review, and improvement. This study revealed a need for blended learning to balance the benefits of face-to-face and online learning. A hybrid learning environment gives students the privilege of understanding and exploring real-world problems through an authentic learning experience and facilitates the online learning experience. This study concludes that COVID-19 has changed instructor teaching strategies to make language teaching more effective. Keywords: blended learning, COVID-19, strategies, methods, Teaching Malay Language.